Charakter więzi prawnych pomiędzy przedsiębiorstwem państwowym i jego dyrektorem - Stefaniuk, Krzysztof (Wydział Prawa i Administracji UAM, 1987)
Director is — in the light of the Law of September 25, 1981 on State Enterprises — an organ of a legal person and at the same time a manager of a plant in the light of labor law. Both legal categories serve to indicate a natural person (persons) authorized to act in the legal sphere of a given economic unit recognized as a subject of law, with the effects falling to that unit (to a legal person, a plant). The legal construct of a director may therefore be perceived and analysed as a set of combined legal relations between an enterprise (a legal person, a plant) and a natural person designated in a specified way as a director. The legal relationship of an organ is a relation under civil law, although its structure and contents differ from typical civil-law relationships, the paradigm of which is the relationship resulting from an obligation. Its contents are the powers of a natural person designated as an organ to undertake legal transactions with effects falling to a legal person, and its function is shaping ("organizing") other civil- law relations of a legal person. In view of the said function, the legal relationship of an organ may be defined as an organizational relationship under civil law. In civil law the relationships of such a kid appear also in the situations other than concerning legal persons; representation is an example of such a relationship. A natural person appointed to be director is linked with an enterprise by an organizational relationship under civil law. With that relationship the organizational relationship under labor law is combined ex lege. It is justified to define the construct of a manager of a plant in this way since it indicates a natural person authorized to organize, on behalf of a plant, the employment relations. Besides, a person appointed director is linked with an enterprise by the employment relation resulting from an obligation, the contents of which is, in particular, the duty of the appropriate use of powers flowing from the two organizational relations mentioned above. In the light of the law in force, the employée status is an inseparable element of the legal status of a director, for it is impossible to appoint a given person to be director — an organ of a legal person and a manager of a plant — without establishing with such a person the employment relationship. The connection of the three types of legal ties within the legal construct of a director is its characteristic feature. In cases of other managing bodies hiring employées such a connection of different ties does not occur. The above basic differences lead to more detailed differences in legal regulation of the director's situation in comparison with eg. the board of a cooperative or of a commercial company. In the light of the Law on Enterprises, it does not seem possible to treat a director as an organ of state administration. He does not act on behalf of State but on behalf of an enterprise and, in principle, he is not equipped with powers to shape imperiously and unilaterally the legal position of other subjects in the sphere of administrative law. On the other hand, he is not officially subordinated to the establishing organ. In turn, the explanation of his personal subordination to that organ lies in the construct of an enterprise as a so-called dependent legal person rather than in the construct of a director as an organ of State administration.
The Character of Legal Relations between a State Enterprise and its Director